(untitled) (PERcursos Linguísticos, 2022)
This text is an excerpt from a larger research that seeks to problematize the emergence and institutionalization of the Libras and Portuguese Translator and Interpreter in the imperative of inclusion. It seeks to understand how deaf resistance modes are produced from the practices and experiences of this professional and reflects on his insertion in the inclusive school context. Narratives of people with experience in the area of translation and interpretation of Libras and Portuguese, aged between 29 and 55 years, from different states of the federation were analyzed. We understand that the Libras and Portuguese Translator and Interpreter has been constituted as a risk management device for deaf subjects in the school space, in the inclusion intelligibility grid, which is responsible for managing the behavior of the subjects classified as the target audience of this rationality. We believe that at different times in their historical trajectory, these subjects resonated in their practices, which I understand as modes of deaf resistance, ways of fighting against the power relations of the controls and regulations of deaf bodies in different spaces.